Static Properties Based Classification of Pneumatic Actuators - Potential of Progressive Effective Area Over the Stroke - Reinertz, Olivier (International Conference Fluid Power 2025: Conference Proceedings, 2025)
A variety of pneumatic actuator principles coexist on the market. The different designs are each dedicated to selected applications due to their specific properties and requirements. This paper aims to analyze the existing solutions by means of their static properties, to reveal innovation potential for new designs with enhanced operational behavior. It is based on a thorough investigation of the underlying physical correlations of force and stiffness. Thereof, a classification of existing principles is achieved, and a barely realized class of actuators with progressive effective area over the stroke is unveiled. A further analysis of the operational behavior of these actuators shows huge potential in selected applications. They are predicted to be superior in terms of performance and efficiency compared to existing solutions. A further analysis of the requirements on the design emphasizes the need for completely different realization concepts in comparison to the existing solutions. Finally, the paper closes by showing possible pathways to solve the actual challenges by incorporating new design methods.